Harm avoidance, daily stress, and problematic smartphone use in children and adolescents - Yoo, So Young; Park, Su Mi; Choi, Chi-Hyun; Chung, Sun Ju; Bhang, Soo-Young; Kim, Jae-Won; Kweon, Yong-Sil; Choi, Jung-Seok (Frontiers in Psychiatry, 2022)
Objective: Temperament is close to susceptibility to stress and the increased level of stress may lead problematic smartphone use (PSU). In this study, the relationships between harm avoidance (HA) as a personality trait, daily traits, and PSU in children and adolescents were investigated. Methods: At baseline, all participants (184 children and adolescents, mean age 13.15 years) completed screening questionnaires on PSU using the Smartphone Addiction Scale-Short Version (SAS-SV) and the Korean Smartphone Addiction Proneness Scale (SAPS). The Daily Hassles Questionnaire (DHQ) and Junior Temperament and Character Inventory (JTCI) were also administered to evaluate stress levels and personality traits. SAS-SV, SAPS, and DHQ were reassessed at 3 and 6 months. Results: Among JTCI temperament, HA displayed robust positive correlations with SAS-SV, SAPS, and DHQ at all time points. Mediation effects of daily stress on the relationship between HA and PSU were observed at baseline, 3, and 6 months. Conclusions: The findings suggest that managing stress may important in PSU children and adolescents with high HA.